Toxicity and Persistency of Thiodicarb Insecticide, on Cotton Plants to Conserve Parasitoid Wasp, Bracon hebetor Say - Badakhshi, Ahmad Jamshied; Niazyar, Azizullah; Hotak, Shamsullah (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Bracon hebetor Say is one of the most important parasitoids of cotton bollworm, Helicoverpa armigera (Hübner) in cotton fields. Using reduced-risk chemicals with low toxicity and persistency, is a principal tool to conserve and increase population of this parasitoid in cotton fields. This study was carried out to investigate residual lethal and sublethal toxicity and persistency of thiodicarb insecticide, on cotton plants against this parasitoid wasp. All experiments were carried out at the Entomological Research and Biological Control Labs. Department of Plant Protection and Greenhouse of the Faculty of Plant Production, Gorgan University of Agricultural Sciences and Natural Resources, Gorgan, Iran. Cotton seeds (variety Golestan) were sown under greenhouse condition and cotton plants were sprayed with insecticides at recommended concentration rates (2000 and 500 ppm, respectively). Sprayed cotton leaves were removed at one-day intervals and female parasitoids were exposed to them within a container under laboratory condition (25±1°C, 60±5% RH, and 16:8 h L: D). The lethal (mortality percent) and sub lethal (reduction in female fecundity and paralyzing ability) effects of each insecticide were recorded every day until the “total effect” (mortality + fecundity reduction) reach to harmless category (<25%), according to IOBC standards. Data were analyzed and means were compared using a completely randomized experimental design and then insecticides toxicity and persistency were categorized according to the IOBC standard classes. Residual lethal toxicity of thiodicarb on B. hebetor (up to 77.9% mortality). Moreover, thiodicarb significantly reduced parasitoid fecundity and paralyzing ability (with 100 and 98.1 percent reductions compared to control, respectively) and was categorized as a harmful insecticide (group 4) based on total effect. Thiodicarb was also highly toxic to immature stages of parasitoid and reduced egg hatching and survival of parasitoid larvae by 95.9% and 82.8%, respectively compared to control. Residual persistency of insecticide was significantly different on cotton plants. Thiodicarb had longer persistency on cotton plants and its “total effect” on parasitoid was more than 25% for 22 days after spraying. Therefore, it was classified as a “moderately persistent” (group 3) insecticide according to the IOBC standard classes. Because of high toxicity and long-term persistency, thiodicarb is not recommended to use in cotton field against cotton bollworm in integrate program with mass release of B. hebetor. Of course, because of adverse effects of thiodicarb on parasitoid fecundity and paralyzing ability, a 25-day waiting period was recommended between spraying with this insecticide and mass releasing of B. hebetor in cotton fields.